Why ASEAN is Cooperating in the Education Sector? - Jan Gawron (Center for Southeast Asian Social Studies (CESASS), 2017)
Over the last few years ASEAN member states have begun collaborating more tightly in the tertiary education sector, which has led to a cooperation agreement with the European Union to help harmonize and lift the overall standard of tertiary education in the region. However, the broader question is - why is that the case? Education is not considered a classical field of regional integration, and this chapter seeks to analyze various sources - which include references from elitist circles, as well as the public sphere - in order to identify the motivation for cooperation in the education sector through qualitative content analysis. The analysis is based on a theoretical framework, which incorporates both a neofunctionalist approach and a norm diffusion approach which show that the predominant factors behind this cooperation process are economic.